A Person-Centered Approach to Action-Control Beliefs of Students With Special Educational Needs and Their Relation to Student Performance and Time on Task - Nyman, Laura; Koivuhovi, Satu; Greiff, Samuel; Hotulainen, Risto; Little, Todd D.; Vainikainen, Mari-Pauliina (American Psychological Association, 2026)
While effort and motivation are crucial for academic success, research on their relation to academic success of students with special educational needs (SEN) is inconclusive, largely due to the heterogeneity of students with SEN and their diverse motivational characteristics. The aim of this study is to address this gap by utilizing person-centered latent profile analysis to identify distinct profiles based on students’ control-related motivational beliefs, and to examine how students’ SEN status is associated with the likelihood of exhibiting certain profiles. In addition, we explore how these motivational profiles differ in terms of student performance, including academic achievement (student-reported grade point average) and cognitive tasks (learning to learn tasks), as well as task behavior, specifically time on task (log data) as an indicator of effort. Analyzing national-level data from Finnish ninth graders with and without SEN status (N = 6,942), four motivational profiles emerged: agentic, moderate, avoidant, and mixed. Although SEN students were depicted in all motivational profiles, they were more likely to belong to profiles demonstrating more maladaptive motivational patterns, less time on task, and lower cognitive task achievement. Through these findings, we highlight the importance of a person-centered approach to students’ beliefs in identifying different reasons and consequences for performance. We also contribute to research on students’ motivational patterns and behavior-related factors explaining differences in task performance that can be further explored using computer-based assessment and log analytics. Educators and policy makers can apply these valuable insights to support students with diverse motivational profiles and learning needs.